If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5P + -10 = 50 + -1P Reorder the terms: -10 + 0.5P = 50 + -1P Solving -10 + 0.5P = 50 + -1P Solving for variable 'P'. Move all terms containing P to the left, all other terms to the right. Add 'P' to each side of the equation. -10 + 0.5P + P = 50 + -1P + P Combine like terms: 0.5P + P = 1.5P -10 + 1.5P = 50 + -1P + P Combine like terms: -1P + P = 0 -10 + 1.5P = 50 + 0 -10 + 1.5P = 50 Add '10' to each side of the equation. -10 + 10 + 1.5P = 50 + 10 Combine like terms: -10 + 10 = 0 0 + 1.5P = 50 + 10 1.5P = 50 + 10 Combine like terms: 50 + 10 = 60 1.5P = 60 Divide each side by '1.5'. P = 40 Simplifying P = 40
| -8-7(r-6)=90 | | d=5m | | 2+5x=6x-8 | | 17x+11=180 | | 18x+4=180 | | x-8=2x-14 | | 16.40=x-020*x | | 1/3x35x7 | | 3x-(6x-4)/2=-2 | | -2.5-3y=-3 | | 9n^2-18n-16=0 | | 5x-2x-2=3x-9 | | 13+11x=360 | | 684=0.14x+0.10(1800+x) | | 11=1-2x | | 0.3x-0.5=0.2x+6 | | a^2-26=0 | | -6*3b+3+19b-6=0 | | 0=2x^2-8x | | 13+11x=180 | | Log^2(x+3)=4 | | 31/2r=28 | | 11x-4=360 | | -4x-11=2(x-3x)+13 | | x+0.10(600-x)=.55(600) | | 13.2=t-4.4 | | 0=-16t^2+38 | | 3n^2-n-14=0 | | 3(7x+4)=21x+21 | | 4m-12=12-2m | | 100=(x*30)*.5 | | 5(3x-9)-9=15x-54 |